Unexpected Solvent Isotope Effect on the Triplet Lifetime of Methylene Blue Associated to Cucurbit[7]Uril - Lissi-Gervaso, E (2012)
Methylene blue shows an isotope dependent triplet lifetime that is 50% longer in D 2O compared with H 2O as a result of electronic-to-vibrational relaxation. The effect is enhanced when the dye is bound to curcubit[7]uril due to a combination of restricted mobility and a unfavorable vibrational coupling. © 2012 The Royal Society of Chemistry and Owner Societies.